Characterization of Black Sesame (Sesamum indicum L.) Genotypes through Capsule Morphology - JG SAVALIYA; CA BABARIYA; JB PATEL (Seed Research, 2026)
An experiment was carried out at the Sagdividi Farm, Department of Seed Science and Technology, Junagadh Agricultural University, Junagadh, to characterize forty black sesame genotypes based on the morphological characters of the capsule. The genotypes were grouped based on the capsule hairiness into three groups namely absent (3 genotypes), sparse (30 genotypes) and dense (7 genotypes). Based on the number of locules per capsule two groups were made i.e., four locules per capsule in (37 genotypes) and six locules per capsule in (3 genotypes). Based on the capsule shape, genotypes were grouped into tapered (13 genotype), narrow oblong (9 genotypes) and broad oblong (18 genotypes) types. Based on the number of capsules per leaf axil, genotypes were grouped into one (36 genotypes) and more than one (4 genotypes) capsules per leaf axil. Based on capsule arrangement, genotypes were grouped into alternate (13 genotypes), opposite (25 genotypes) and cluster (2 genotypes) types. Based on variation in number of capsules per plant, genotypes were grouped into two categories as, moderate (33 genotypes) and less (7 genotypes). Based on variation in capsule length, genotypes were grouped into two categories as medium (30 genotypes) and long (10 genotypes). Based on the beak of capsule, genotypes were grouped as, short (14 genotypes) and long (26 genotypes) beaked types.